FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN FOOD AND BEVERAGES - Tamara, Yeremia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This research is carried out to test the influence of assets structure, growth, and profitability to the capital structure of food and beverages companies in Indonesia Stock Exchange from 2010 to 2012. The research samples are 14 food and beverages companies which have been selected by using purposive sampling. The result of the research shows that overall this research regression model has fulfilled classic assumption test which means that this regression model is free from the existence of heteroscedasticity, multicollinearity, and autocorrelation symptoms and the generated data has been normally distributed. The multiple regression analysis shows that assets structure variable has no significant structure to the capital structure, growth variable has significant influence to the capital structure, and profitability has no significant structure to the capital structure.Keywords: Assets Structure, Growth, Profitability, and Capital Structure